THE ROLE OF EDUCATION OUT OF SCHOOL IN HUMAN RESOURCES DEVELOPMENT - Ninik Sudarwati (Indonesian Journal of Education and Learning, 2021)
The Indonesian government is currently working on improving the quality of human resources so that our country is not far behind overseas and can compete in any field. One of the important factors in improving the quality of human resources is through education. The low quality of human resources can be caused by economic factors. The government moves the Non-School Education program to provide skills for citizens of productive age. The research method used is a qualitative research approach and descriptive research type, the data collection techniques used are literature / literature review, articles. Human resource development is influenced by education, one of which is out-of-school education. Outside school education that is designed to teach citizens to learn to have the types of skills and / or knowledge and experience that are carried out outside the formal education pathway. Efforts to improve human resources require cooperation from parties, especially the provision of education and expertise in accordance with standards set by the government. Quality human resources, targets in Indonesia's development will be easier to achieve.